ANALISIS HUBUNGAN BEBAN KERJA MENTAL DENGAN KINERJA KARYAWAN SMK BATIK 1 SURAKARTA - Septyani Kartikaningsih; Nancy Oktyajati, Sri Mayasari (PROSIDING, 2022)
. This thesis discusses the relationship between the mental workload of employees at SMK Batik 1 Surakarta. The methodology used is quantitative research using survey method with total sampling, Subjective Workload Assessment (SWAT) technique, and sample method for several employees at SMK Batik 1 Surakarta. The sampling results show that most teachers perform non-productive activities during working hours that exceed the allowances provided. Physical stress is a more significant factor in the performance of employees in the administration of student payment receipts. On the other hand, the Mental Effort (E) factor interferes with performance in managing financial affairs, including paying tuition fees that must be carried out at the end of the semester. Based on the results of this workload research, it is expected that the company can divide tasks and allocate employees better. Keywords: Workload, Mental Workload, Employee Performance, SWAT